Microwave Principles in the Modelling of Radar Antennas for Automotive Applications (Global Journals of Research in Engineering, 2016)
In this paper we devise a general model in determining several salient parameters that have an effect on the 24 GHz radar antenna. This method is also applicable to several antenna design areas such as the satellite communication in the Ku band and C-band but our focus is mainly on the 24 GHz and 77GHz radar
Keywords: antenna radiation patterns; radio frequency; radar